Persistent variations in national asthma mortality, hospital admissions and prevalence by socioeconomic status and region in England. Issue 8 (14th May 2018) - Gupta, Ramyani P; Mukherjee, Mome; Sheikh, Aziz; Strachan, David P
Abstract : Background: The UK-wide National Review of Asthma Deaths sought to identify avoidable factors from the high numbers of deaths, but did not examine variation by socioeconomic status (SES) or region. Methods: We used asthma deaths in England over the period 2002–2015 obtained from national deaths registers, summarised by quintiles of Index of Multiple Deprivation (IMD) and Government Office Region. Emergency asthma admissions were obtained from Hospital Episode Statistics for England 2001–2011. The prevalence of asthma was derived from the Health Survey for England 2010. Associations of mortality, admissions and prevalence with IMD quintile and region were estimated cross-sectionally using incidence rate ratios (IRRs) adjusted for age and sex and, where possible, smoking. Results: Asthma mortality decreased among more deprived groups at younger ages. Among 5–44 year olds, those in the most deprived quintile, mortality was 19% lower than those in the least deprived quintile (IRR 0.81 (95% CI 0.69 to 0.96). In older adults, this pattern was reversed (45–74 years: IRR 1.37 (1.24–1.52), ≥75 years: IRR 1.30 (1.22–1.39)). In 5–44 year olds the inverse trend with asthma mortality contrasted with large positive associations for admissions (IRR 3.34 (3.30–3.38)) and prevalence of severe symptoms (IRR 2.38 (1.70–3.33)). Prevalence trends remained after adjustment for smoking. IRRs for asthma mortality, admissions and prevalence showed significant heterogeneity between English regions. Conclusions: Despite asthma mortality, emergency admissions and prevalence decreasing over recent decades, England still experiences significant SES and regional variations. The previously undocumented inverse relation between deprivation and mortality in the young requires further investigation.